Anti-Xa–guided enoxaparin thromboprophylaxis reduces rate of deep venous thromboembolism in high-risk trauma patients. Issue 6 (December 2016) - Singer, George A.; Riggi, Gina; Karcutskie, Charles A.; Vaghaiwalla, Tanaz M.; Lieberman, Howard M.; Ginzburg, Enrique; Namias, Nicholas; Lineen, Edward B.
Abstract : BACKGROUND: Appropriate prophylaxis against venous thromboembolism (VTE) remains undefined. This study evaluated an anti-Xa–guided enoxaparin thromboprophylaxis (TPX) protocol on the incidence of VTE in high-risk trauma patients based on Greenfield's Risk Assessment Profile (RAP) score. METHODS: This is a retrospective observational study of patients admitted to a trauma intensive care unit over a 12-month period. Patients were included if they received anti-Xa–guided enoxaparin TPX. Dosage was adjusted to a prophylactic peak anti-Xa level of 0.2 to 0.4 IU/mL. Subgroup analysis was performed on high-risk patients (RAP score ≥10) who received lower-extremity duplex ultrasound surveillance for deep vein thrombosis (DVT). Data are expressed as mean ± SD. Significance was assessed at p < 0.05. RESULTS: One hundred thirty-one patients received anti-Xa–guided enoxaparin TPX. Four patients were excluded for age or acute VTE on admission. Fifty-six patients with RAP score of ≥10 and surveillance duplex evaluations were included in the subgroup analysis with mean age 43 ± 20 years, Injury Severity Score of 25 ± 10, and RAP score of 16 ± 4. Prophylactic anti-Xa levels were initially achieved in 34.6% of patients. An additional 25.2% required 40 to 60 mg twice daily to reach prophylactic levels; 39.4% never reached prophylactic levels. Weight, body mass index, ISS, and RAP score were significantly higher with subprophylactic anti-Xa levels. One patient developed bleeding complications (0.8%). No patient developed intracerebral bleeding or heparin-induced thrombocytopenia. Nine VTE events occurred in the high-risk subgroup, including four DVT (7.1%), all asymptomatic, and five pulmonary emboli (8.9%). The historical rate of DVT in similar patients (ISS 31 ± 12 and RAP score 16 ± 5) was 20.5%, a significant decrease ( p = 0.031). Mean chest Abbreviated Injury Scale scores were significantly higher for patients developing pulmonary emboli than DVT, 3.0 ± 1.1 vs. 0.0 ( p < 0.001). CONCLUSIONS: Mean chest Abbreviated Injury Scale score was higher in patients developing pulmonary embolism. Increased weight, body mass index, ISS, and RAP score are associated with subprophylactic anti-Xa levels. Anti-Xa–guided enoxaparin dosing reduced the rate of DVT from 20.5% to 7.1% in high-risk trauma patients. LEVEL OF EVIDENCE: Therapeutic study, level IV.